Complementary and alternative medicine (CAM) for epilepsy treatment in the Middle East and North Africa (MENA) region - Boulenouar Mesraoua (16936932) (2021)
Introduction The aim of this study is to provide the reader with a review on Complementary and Alternative Medicine (CAM) treatment in epilepsy in the Middle East and North Africa (MENA) region, to describe the extent and factors associated with its use among patients with epilepsy (PWE), and to recommend how effectively we will be able to reduce this alarming use. Material and Methods Retrospective literature search from 1945 to December 2019, regarding CAM use in the MENA region, using electronic databases (PubMed, Scopus, Google Scholar, Web of Science). Conclusion The use of CAM and consultation of traditional healers for the treatment of epilepsy has so far been widespread practice for centuries in the MENA region. Lack of health professionals and non-adherence to conventional epilepsy treatment are strongly associated with the use of CAM. Improvement in the level of knowledge of epilepsy among PWE, healthcare professionals, including traditional healers, will educate PWE and their caregivers on potentially unsafe practices and promote adherence to Antiseizure Drugs (ASDs). Additionally, randomized controlled trials are needed to study the role and value of various CAM treatment options in PWEs. Other Information Published in: Epilepsy Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eplepsyres.2020.106538